A Structural Analysis of Energy Intensity Change in Malaysia - Bekhet, Hussain Ali; Abdullah, Azlina (International Journal of Energy Economics and Policy, 2017)
This research investigates the changes in Malaysia's energy intensity for the 2005-2010 period using structural decomposition analysis. Five contributing factors for energy intensity change namely energy mix, sectoral energy efficiency, production structure, final demand structure and final demand components are analysed. Results demonstrate that energy intensity has decreased but only at a minimal level. The prominent factor responsible for the decline was final demand components mainly due to the lower exports of the country as a result of the 2007/2008 global financial crisis. The production structure factor also contributed to a further decline in energy intensity which can be supported by the stronger dominant role played by services sector which is less energy intensive in addition to the lower contribution of manufacturing sector to gross domestic product. A larger decline in energy intensity was dampened by the positive effects demonstrated by the sectoral energy efficiency and final demand structure factors. The energy mix factor has also contributed to an upsurge in energy intensity but only at a minimal extent. Based on the research findings, several policy implications are highlighted to help Malaysia in achieving its sustainable energy use in the future. Keywords: Energy Intensity, Energy Efficiency, Structural Decomposition Analysis, Input-output Model, Malaysia JEL Classifications: C67, O44, Q43